Impacto de diferentes coeficientes de assimetria em conversores multiníveis com uma fonte CC - Castiblanco, Wilmar Armando Pineda (2017)
Multilevel converters operating with single dc source represent an interesting and simple solution, since only an isolated voltage source is required, even in applications with active power transfer. In this way, the converter analyzed in this dissertation is composed of the three-phase three-level main converter with neutral point clamped (NPC) powered by an isolate voltage source. In addition, single-phase full-bridge (FB) auxiliary cells, supplied by floating capacitors, are connected in series at each stage to increase the number of synthesized levels. Different asymmetric coefficients between voltages on the main cells and the auxiliary cells in series are exploited to synthesized waveforms with lower harmonic content and reduce the stress on the auxiliary cells. Also, the limitations imposed by the modulation strategy are considered, in which the main high-voltage converter operate with the fundamental frequency of the reference ac voltage, the impact of these limitations on the operation of the low-voltage auxiliary cells, which operate with pulsed-width modulation and should not process active power is evaluated. As a result, over-modulation regions are revealed in the auxiliary cells operation from the energy error between the reference signals and the maximum signal that can be synthesized by the multilevel converter. In this way, for a high asymmetric coefficient, the choice of an over-modulation region with minimal error signal energy reduces the harmonic distortion on the line-to-line voltages but also with the benefic, that the auxiliary cells will exposed to lower blocking voltages. Finally, results for single dc source converter applied to the input rectifier stage the speed drive system and operating with high asymmetric coefficient in a region with minimal energy error signal are included.